HOTEL STRATEGY USING STAYCATION MARKETING IN FACING THE COVID-19 PANDEMIC - Okky Rizal Ridwan; Ahmad Hudaiby Galih Kusumah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
This research was conducted to find out how the form of staycation marketing carried out by the hotel and how the results and evaluation of the marketing activities carried out. The sample studied amounted to 6 people who are hotel employees who know the marketing activities carried out and how the level of guest visits during staycation marketing is carried out. This study uses a qualitative method to dig deeper into how hotels conduct staycation marketing during the pandemic, which is deepened by interviews conducted by digital telephone that focus on â€œhowâ€ questions to encourage samples to share how hotels survive during the pandemic and how staycation marketing activities are carried out. The result is that the COVID-19 pandemic has had a negative impact on the hospitality industry, especially with low income, strategies to survive during the pandemic are the key for properties to remain standing, carry out staycation marketing activities through social media and websites with creative and attractive content, as well as providing packages and services. price cuts. The results and evaluation of this marketing activity have a good impact on the room occupancy rate, but the increase is not significant, at least there is hope.